Deep into Pharo - Bergel, Alexandre; Cassou, Damien; Ducasse, Stéphane; Laval, Jannik (Open textbook library., 2013)
Pharo is a clean, innovative, open-source, live-programming environment. Deep into Pharois the second volume of a series of books covering Pharo. Whereas the first volume is intended for newcomers, this second volume covers deeper topics.You will learn about Pharo frameworks and libraries such as Glamour, PetitParser, Roassal, FileSystem, Regex, and Socket. You will explore the language with chapters on exceptions, blocks, small integers, and floats. You will discover tools such as profilers, Metacello and Gofer.